METODE DAKWAH LANGGAR PESANTREN ASSHIDDIQI JEPARA - Noor Rohman Fauzan (An-Nida : Jurnal Komunikasi Islam, 2022)
This study seeks to describe the da'wah method used in Langgar Pesantren Assidiqi in its da'wah activities to the bat students. By using qualitative description method, data collection by observation, interview and documentation. The results showed that the method used in da'wah activities by the dai (kyai), administrators with the lecture method, good advice, and role models. However, of the three methods of da'wah, each has its advantages and disadvantages in the implementation of da'wah.